14-3-3 Protein of Neospora caninum Modulates Host Cell Innate Immunity Through the Activation of MAPK and NF-κB Pathways - Li, Shan; Gong, Pengtao; Zhang, Nan; Li, Xin; Tai, Lixin; Wang, Xu; Yang, Zhengtao; Yang, Ju; Zhu, Xingquan; Zhang, Xichen; Li, Jianhua (Frontiers in Microbiology, 2019)
Neospora caninum is an obligate intracellular apicomplexan parasite, the etiologic agent of neosporosis, and a major cause of reproductive loss in cattle. There is still a lack of effective prevention and treatment measures. The 14-3-3 protein is a widely expressed acidic protein that spontaneously forms dimers within apicomplexan parasites. This protein has been isolated and sequenced in many parasites; however, there are few reports about the N. caninum 14-3-3 protein. Here, we successfully expressed and purified a recombinant fusion protein of Nc14-3-3 (rNc14-3-3) and prepared a polyclonal antibody. Immunofluorescence and immunogold electron microscopy studies of tachyzoites or N. caninum-infected cells suggested that 14-3-3 was localized in the cytosol and the membrane. Western blotting analysis indicated that rNc14-3-3 could be recognized by N. caninum-infected mouse sera, suggesting that 14-3-3 may be an infection-associated antigen that is involved in the host immune response. We demonstrated that rNc14-3-3 induced cytokine expression by activating the MAPK and AKT signaling pathways, and inhibitors of p38, ERK, JNK and AKT could significantly decrease the production of IL-6, IL-12p40 and TNF-α. In addition, phosphorylated nuclear factor-κB (NF-κB/p65) was observed in wild-type peritoneal macrophages treated with rNc14-3-3, and the protein level of NF-κB/p65 was reduced in the cytoplasm but increased correspondingly in the nucleus after 2 h of treatment. These results were also observed in deficient in TLR2-/- peritoneal macrophages. Taken together, our results indicated that the N. caninum 14-3-3 protein can induce effective immune responses and stimulate cytokine expression by activating the MAPK, AKT and NF-κB signaling pathways but did not dependent TLR2, suggesting that Nc14-3-3 is a novel vaccine candidate against neosporosis.